Representaciones gráficas del futuro en revistas de ciencia ficción argentinas publicadas en la década de 1950 - Elfenbaum, Wanda (2022)
This paper offers an analysis of a series of graphic representations of the future published in the Argentine science fiction magazine Más Allá de la ciencia y de la fantasía, in Buenos Aires, during the 1950s. From a sociocultural perspective that contemplates the historical moment in which these visions of the future were produced, and through their relationship with other visual devices that operated as conditions of production and recognition for them, it was possible to establish a landscape of the visions of technology that were constructed by science fiction of that period, as well as the categories, topics and visual cues that were employed to represent the idea of the future. It was also possible to verify that the ideas of the future were built around what was familiar and known, following the major technological advances of the time, real or potential: space travel and atomic energy. These two topics were the starting point for a range of speculations on possible scenarios of progress, conquest and destruction, reflecting the problems, fears and desires of the present from which they were imagined.